2017
DOI: 10.3389/fncir.2017.00059
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine Release in the Cat Lumbar Spinal Cord during Fictive Locomotion Evoked by the Mesencephalic Locomotor Region

Abstract: Spinal cord neurons active during locomotion are innervated by descending axons that release the monoamines serotonin (5-HT) and norepinephrine (NE) and these neurons express monoaminergic receptor subtypes implicated in the control of locomotion. The timing, level and spinal locations of release of these two substances during centrally-generated locomotor activity should therefore be critical to this control. These variables were measured in real time by fast-cyclic voltammetry in the decerebrate cat’s lumbar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 170 publications
(317 reference statements)
3
40
0
Order By: Relevance
“…It was later shown that noradrenaline is indeed released by stimulation of MLR (249). These effects are conveyed via the coeruleospinal pathway via ␣ 2 -and ␤ 2 -receptors (360). Although the noradrenergic system thus can contribute, locomotion can still be elicited after it has been inactivated (429).…”
Section: Modulator Action Via the Noradrenergic System Contributes Tomentioning
confidence: 99%
See 1 more Smart Citation
“…It was later shown that noradrenaline is indeed released by stimulation of MLR (249). These effects are conveyed via the coeruleospinal pathway via ␣ 2 -and ␤ 2 -receptors (360). Although the noradrenergic system thus can contribute, locomotion can still be elicited after it has been inactivated (429).…”
Section: Modulator Action Via the Noradrenergic System Contributes Tomentioning
confidence: 99%
“…The effects of 5-HT precursors have similar, but not identical, effects to that of DOPA, suggesting a 5-HT involvement in the control of locomotor circuits (10,11). In rodents and cats, it has been shown that 5-HT neurons in the raphe magnus nucleus are activated, when locomotor activity is turned on from for instance MLR or spontaneously (80), and that 5-HT is released in the spinal cord (360). These effects are mediated by both 5-HT 1a and 5-HT 7 receptor subtypes.…”
Section: Modulator Action Via the 5-ht System Contributes To Spinal Lmentioning
confidence: 99%
“…These serotoninergic pathways could originate either from brainstem neurons giving rise to the descending tracts (Jordan et al, 2008) or from propriospinal interneurons (Cabaj et al, 2017). Some studies have reported that monoamines are strong modulators and/or activators of the spinal locomotor networks (Noga et al, 2009(Noga et al, , 2017, although they are not necessary to evoke locomotion (Steeves et al, 1980). Sustained monoamine release activates receptors in neurons within the spinal cord, suggesting sustained extrasynaptic transmission (Noga et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One possible candidate is synaptic 67 short term depression (STD) to repetitive synaptic activation. For the STD to be able 68 to create alternating oscillatory output, it needs to be at the center of two circuitry 69 components connected by reciprocal inhibition, just like in the classical half center 70 model. This mechanism has been proposed as the self-inhibitory mechanism to explain 71 alternating oscillation in the spinal cord of the lamprey [30].…”
Section: Introductionmentioning
confidence: 99%
“…The 326 neuromodulator 5-HT promotes persistent inward currents [69], so that even in an in 327 vivo experiment the neurons could be made to behave like in an in vitro setting, where 328 intrinsic conductances become more dominant than the total synaptic input activity to 329 the neuron. In another set of preparations [24,70] the animal was also paralyzed and 330 fictive locomotion was evoked by stimulation of the mesencephalic locomotor region. In 331 this case it cannot be excluded that the oscillatory behavior in the spinal neurons is due 332 to the descending activation from the brainstem.…”
mentioning
confidence: 99%